Framing of Electoral Processes: The Stages of the Campaign as a Moderator of the Presence of Political Frames in the News - Muñiz, Carlos; Saldierna, Alma Rosa; Marañón Lazcano, Felipe de Jesús (Universidad de la Sabana, 2018)
Abstract Mass media plays a crucial role during the election campaigns, because, by promoting a particular framing to present issues and candidates involved in the campaigns citizens are granted access to the political debate. To analyze the political framing carried out by the media during the 2015 gubernatorial election campaign of Nuevo León, Mexico, a content analysis of the news stories published by television and the press was developed. Findings made it possible to detect a different use of news frames by both media. While the frame of strategic game dominated in television, the press emphasized a treatment of conflict. In addition, a moderation effect of the campaign stages was observed in the use of different news frames, increasing the use of strategic game and debate and political agreement frames by television, while the press maintained a constant presence of news frames. Keywords Framing; news frames; elections campaign; press; television (Source: Unesco Thesaurus).